(untitled) (Third Sector Social Economic Review, 2021)
The aim of this research is to determine and compare the environmental behavior and intellectual tendencies of teacher candidates in different branches. This research was designed in the type of causal comparison, which is one of the quantitative research types. In this context, data were collected from a total of 259 teacher candidates studying at the Faculty of Education of Yozgat Bozok University. An easily accessible sample type was preferred in data collection. “Environmental Attitude Scale” developed by Uzun and Sağlam (2006) was used as a data collection tool. Environmental Attitude Scale consists of 2 factors and a total of 27 items. Factors were defined as “Environmental Behavior Sub-Scale” (13 items) and “Environmental Thinking Sub-Scale” (14). As a result of the analyzes made, it was found that the mean of the intellectual dimension (X = 2.97) was less than the behavioral dimension (X = 4.53) in terms of pre-service teachers’ attitudes towards the environment. In addition, pre-service teachers’ attitudes towards the environment were analyzed in terms of gender, club participation and living place. Within the framework of the data obtained within the scope of this research, it would be beneficial to organize various trainings in order to improve the intellectual and behavioral attitudes of teacher candidates towards the environment.>